Preparation method and application of coating material for enhancing light spot interaction effect of electronic display screen and laser pen
The coating material combining nanotitanium dioxide with aqueous polyurethane was prepared by the in-situ modification method of citric acid, which solved the problem of poor interaction of laser point points in electronic display screens at large angles, and achieved the effect of significantly enhancing the interaction effect at various angles.
Patent Information
- Application Number
- CN202411935948.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-14
AI Technical Summary
Due to its high glass-transmissive surface and low reflectivity, participants cannot clearly see the highlight indicator of the laser point on the screen within a large angle range.
Nanotitanium dioxide was prepared by in-situ modification of citric acid, combined with aqueous polyurethane emulsion, and prepared a nanocomposite polyurethane coating material, and applied it to the resin base film to form an optical film material to improve diffuse reflection performance.
While ensuring transparency, the interaction effect of the electronic display screen and the laser point light spots is significantly improved, so that the laser point light spots can be clearly seen at all angles.
Smart Images

Figure CN119614058A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of composite material coatings, and in particular relates to a preparation method and application of a coating material for enhancing the interaction effect between an electronic display screen and a laser pen light spot. Background Art
[0002] Electronic display screens are becoming increasingly popular in daily work and life. Large-area display systems are required in many application scenarios such as daily lectures and meetings, and are used in conjunction with laser pens and other highlight indication devices to highlight the content of the lecture. The electronic display screen is composed of a large number of colored light-emitting diodes, which absorb light themselves, so the reflectivity to other light sources, especially laser pens, is extremely low. In addition, its outermost layer is composed of highly transparent glass. The mirror reflection on the smooth glass surface is relatively strong, while the diffuse reflection is relatively weak. When the path of the incident light is certain, the reflected light can only be clearly seen at a specific angle. Therefore, in actual application scenarios, there is a problem that participants cannot clearly see the highlight indication of the laser pen's light spot on the electronic display screen within a large angle range. Summary of the invention
[0003] The purpose of the present invention is to address the above-mentioned technical problems and provide a method for preparing a coating material for enhancing the interaction effect between an electronic display screen and a laser pen light spot and its application, thereby achieving the effect of enhancing the interaction effect between the electronic display screen and the laser pen light spot at all angles.
[0004] In view of this, the present invention provides a method for preparing a coating material for enhancing the interaction effect between an electronic display screen and a laser pen light spot, comprising the following steps:
[0005] S1: Tetrabutyl titanate, anhydrous ethanol, glacial acetic acid, citric acid and water are mixed in a certain proportion to form a mixed solution, and then the mixed solution is fully stirred and mixed;
[0006] S2: placing the fully stirred and mixed solution into a hydrothermal kettle with a polytetrafluoroethylene liner, and placing the hydrothermal kettle in an oven for heating;
[0007] S3: After the reaction is completed, the precipitate is washed by centrifugation, dispersed in water, adjusted to alkaline, and ultrasonically dispersed to obtain a transparent nano-oxide dispersion;
[0008] S4: Mix the transparent nano oxide dispersion with the aqueous polyurethane emulsion, perform ultrasonication, and perform rotary evaporation to remove excess water to obtain a nano composite polyurethane coating material.
[0009] In this technical solution, the titanium dioxide prepared by the in-situ modification method of citric acid can greatly save time and improve the modification efficiency compared with the common modification method of citric acid; and the in-situ modification method can obtain nano titanium dioxide with smaller particle size and narrower particle size distribution, thereby obtaining a more transparent and stable aqueous dispersion in the alkaline range. The titanium dioxide aqueous dispersion is blended with waterborne polyurethane to obtain a nano-composite polyurethane coating material, and the refractive index of the nano-composite polyurethane coating is adjusted by the high refractive index and addition amount of titanium dioxide, thereby adjusting the diffuse reflection performance of the composite material; the nano-composite polyurethane coating is applied to the resin base film to obtain an optical film material, which improves the diffuse reflection performance of the film material while ensuring transparency, thereby enhancing the interactive effect between the electronic display screen and the laser pen light spot at all angles.
[0010] Furthermore, in step S1, the mass ratio of tetrabutyl titanate, anhydrous ethanol, glacial acetic acid, citric acid, and water is 0.98:23.68:1.04:0.2-1:1.2.
[0011] Furthermore, in step S3, the pH value is adjusted to an alkaline range of 8-11.
[0012] Furthermore, in step S4, the rotary evaporation speed is 70 r / min and the temperature is 50° C.-70° C.
[0013] Furthermore, in step S4, the mixing ratio of the nano-oxide dispersion and the aqueous polyurethane emulsion is such that the mass percentage of the nano-titanium oxide to the mass percentage of the aqueous polyurethane is greater than 0wt% and less than or equal to 5wt%.
[0014] Furthermore, in step S4, the mixing ratio of the nano-oxide dispersion and the aqueous polyurethane emulsion is 1 wt % of the mass of the nano-titanium oxide to the mass of the aqueous polyurethane.
[0015] Furthermore, a coating material is prepared by using the coating material preparation method.
[0016] Furthermore, an optical film material is obtained by applying the coating material to the surface of a substrate and curing it.
[0017] Furthermore, the substrate is PC, PET or PVC.
[0018] Furthermore, the coating thickness of the nano-composite polyurethane coating material on the surface of the substrate is 25 μm-300 μm.
[0019] Furthermore, the coating thickness of the nano-composite polyurethane coating material on the surface of the substrate is 200 μm.
[0020] The beneficial effects of the present invention are:
[0021] 1. The titanium dioxide prepared by the in-situ modification method of citric acid can greatly save time and improve the modification efficiency compared with the common modification method of citric acid; and the in-situ modification method can obtain nano titanium dioxide with smaller particle size and narrower particle size distribution, thereby obtaining a more transparent and stable aqueous dispersion in the alkaline range. The titanium dioxide aqueous dispersion is blended with waterborne polyurethane to obtain a nano-composite polyurethane coating material, and the refractive index of the nano-composite polyurethane coating is adjusted by the high refractive index and addition amount of titanium dioxide, thereby adjusting the diffuse reflection performance of the composite material; the nano-composite polyurethane coating is applied to the resin base film to obtain an optical film material, which improves the diffuse reflection performance of the film material while ensuring transparency, thereby enhancing the interactive effect between the electronic display screen and the laser pen light spot at all angles. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is an electron micrograph of titanium dioxide in situ modified by citric acid.
[0023] Figure 2 This is a physical picture of the nano-composite polyurethane coating material.
[0024] Figure 3 This is the transmittance curve of nano-composite polyurethane coating.
[0025] Figure 4 This is the reflectivity curve of nano-composite polyurethane coating.
[0026] Figure 5 This is the application effect diagram of optical film materials coated with nano-composite polyurethane coating with different nanoparticle contents. DETAILED DESCRIPTION
[0027] The technical solutions in the embodiments of the present application will be described clearly below. Obviously, the described embodiments are part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by ordinary technicians in this field based on the embodiments in the present application belong to the scope of protection of the present application.
[0028] In the description of the present application, it should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present application. The techniques, methods and devices known to those of ordinary skill in the relevant art may not be discussed in detail, but in appropriate cases, the techniques, methods and devices should be considered as part of the authorization specification. In all examples shown and discussed here, any specific value should be interpreted as being merely exemplary and not as a limitation. Therefore, other examples of the exemplary embodiments may have different values.
[0029] It should be noted that the terms "first", "second", etc. in the specification and claims of this application are used to distinguish similar objects, but not to describe a specific order or sequence. Moreover, the objects distinguished by "first", "second", etc. are usually of the same type, and the number of objects is not limited. For example, the first object can be one or more. In addition, "and / or" in the specification and claims means at least one of the connected objects, and the character " / " generally means that the objects connected before and after are in an "or" relationship.
[0030] It should be noted that, in the present application, the terms "comprise", "include" or any other variant thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, an element defined by the sentence "comprises one..." does not exclude the presence of other identical elements in the process, method, article or device including the element. In addition, it should be noted that the scope of the method and device in the embodiment of the present application is not limited to performing functions in the order shown or discussed, and may also include performing functions in a substantially simultaneous manner or in reverse order according to the functions involved, for example, the described method may be performed in an order different from that described, and various steps may also be added, omitted, or combined. In addition, the features described with reference to certain examples may be combined in other examples.
[0031] Embodiment 1
[0032] Add 20 mL of anhydrous ethanol, 1 mL of glacial acetic acid, and 10 mL of tetrabutyl titanate to a beaker and mix thoroughly to obtain solution A. Then add 10 mL of anhydrous ethanol and 1.2 mL of water to another beaker and mix thoroughly to obtain solution B. Add solution B dropwise to solution A and mix thoroughly to obtain solution C. Add 0.5 g of citric acid to solution C and stir thoroughly to obtain solution D.
[0033] The fully mixed D solution was transferred into a hydrothermal kettle with a polytetrafluoroethylene liner, and the hydrothermal kettle was placed in an oven for heating at 180°C for 15 hours for reaction;
[0034] After the reaction is completed, the lower precipitate is removed, anhydrous ethanol is added and stirred to obtain a mixed solution, and the mixed solution is centrifuged at 10000 rpm for 5 minutes to obtain a modified nano titanium oxide precipitate; the precipitate is dispersed in water to form a dispersion with a mass concentration of 5wt%, the pH is adjusted to about 10 with a 0.1M NaOH solution, and a transparent nano oxide dispersion is obtained by ultrasonic dispersion;
[0035] The nano-oxide dispersion is mixed with the aqueous polyurethane emulsion so that the mass of the nano-titanium oxide accounts for 1wt% of the mass of the polyurethane, and then the mixture is fully mixed by ultrasonication; the mixed solution is subjected to rotary evaporation at 60°C and 70rpm to remove excess water to obtain a nano-composite polyurethane coating;
[0036] The nano-composite polyurethane coating is applied to a glass substrate with a coating thickness of 200μm. After curing, its transmittance and reflectivity are measured, and the transmittance in the visible light range is about 80%, the transmittance is 86% at a wavelength of 500nm, and the reflectivity is 56.3% (635nm); the nano-composite polyurethane coating is applied to a resin substrate such as PC with a coating thickness of 200μm, and affixed to an electronic display screen to significantly enhance the interaction effect between the electronic display screen and the laser pen light spot.
[0037] Embodiment 2
[0038] Add 20 mL of anhydrous ethanol, 1 mL of glacial acetic acid, and 10 mL of tetrabutyl titanate to a beaker and mix thoroughly to obtain solution A. Then add 10 mL of anhydrous ethanol and 1.2 mL of water to another beaker and mix thoroughly to obtain solution B. Add solution B dropwise to solution A and mix thoroughly to obtain solution C. Add 0.5 g of citric acid to solution C and stir thoroughly to obtain solution D.
[0039] The fully mixed D solution was transferred into a hydrothermal kettle with a polytetrafluoroethylene liner, and the hydrothermal kettle was placed in an oven for heating at 180°C for 15 hours for reaction;
[0040] After the reaction is completed, the lower precipitate is removed, anhydrous ethanol is added and stirred to obtain a mixed solution, and the mixed solution is centrifuged at 10000 rpm for 5 minutes to obtain a modified nano titanium oxide precipitate; the precipitate is dispersed in water to form a dispersion with a mass concentration of 5wt%, the pH is adjusted to about 10 with a 0.1M NaOH solution, and a transparent nano oxide dispersion is obtained by ultrasonic dispersion;
[0041] The nano-oxide dispersion is mixed with the aqueous polyurethane emulsion so that the mass of the nano-titanium oxide accounts for 0.5wt% of the mass of the polyurethane, and then the mixture is fully mixed by ultrasonication; the mixed solution is subjected to rotary evaporation at 60° C. and 70 rpm to remove excess water to obtain a nano-composite polyurethane coating;
[0042] The nano-composite polyurethane coating was applied to a glass substrate with a coating thickness of 200 μm. Its transmittance and reflectivity were measured after curing, and the transmittance in the visible light range was above 80%, the transmittance was 90% at a wavelength of 500 nm, and the reflectivity was 53.7% (635 nm). The nano-composite polyurethane coating was applied to a resin substrate such as PC with a coating thickness of 200 μm and affixed to an electronic display screen, but the enhancement effect on the interaction between the electronic display screen and the laser pen light spot was not obvious.
[0043] Embodiment 3
[0044] Add 20 mL of anhydrous ethanol, 1 mL of glacial acetic acid, and 10 mL of tetrabutyl titanate to a beaker and mix thoroughly to obtain solution A. Then add 10 mL of anhydrous ethanol and 1.2 mL of water to another beaker and mix thoroughly to obtain solution B. Add solution B dropwise to solution A and mix thoroughly to obtain solution C. Add 0.5 g of citric acid to solution C and stir thoroughly to obtain solution D.
[0045] The fully mixed D solution was transferred into a hydrothermal kettle with a polytetrafluoroethylene liner, and the hydrothermal kettle was placed in an oven for heating at 180°C for 15 hours for reaction;
[0046] After the reaction is completed, the lower precipitate is removed, anhydrous ethanol is added and stirred to obtain a mixed solution, and the mixed solution is centrifuged at 10000 rpm for 5 minutes to obtain a modified nano titanium oxide precipitate; the precipitate is dispersed in water to form a dispersion with a mass concentration of 5wt%, the pH is adjusted to about 10 with a 0.1M NaOH solution, and a transparent nano oxide dispersion is obtained by ultrasonic dispersion;
[0047] The nano-oxide dispersion is mixed with the aqueous polyurethane emulsion so that the mass of the nano-titanium oxide accounts for 3wt% of the mass of the polyurethane, and then the mixture is fully mixed by ultrasonication; the mixed solution is subjected to rotary evaporation at 60° C. and 70 rpm to remove excess water to obtain a nano-composite polyurethane coating;
[0048] The nano-composite polyurethane coating is applied to a glass substrate with a coating thickness of 200 μm. Its transmittance and reflectivity are measured after curing, and it is found that the transparency in the visible light range is significantly reduced, and the transmittance fluctuates greatly between 50% and 92%. The transmittance is 72% at a wavelength of 500nm, and the reflectivity is 56.1% (635nm); the nano-composite polyurethane coating is applied to a resin substrate such as PC with a coating thickness of 200 μm. Affixing it to an electronic display screen can significantly enhance the interaction effect between the electronic display screen and the laser pen light spot, but the low transparency affects the content presentation effect of the electronic display screen.
[0049] Embodiment 4
[0050] Add 20 mL of anhydrous ethanol, 1 mL of glacial acetic acid, and 10 mL of tetrabutyl titanate to a beaker and mix thoroughly to obtain solution A. Then add 10 mL of anhydrous ethanol and 1.2 mL of water to another beaker and mix thoroughly to obtain solution B. Add solution B dropwise to solution A and mix thoroughly to obtain solution C. Add 0.5 g of citric acid to solution C and stir thoroughly to obtain solution D.
[0051] The fully mixed D solution was transferred into a hydrothermal kettle with a polytetrafluoroethylene liner, and the hydrothermal kettle was placed in an oven for heating at 180°C for 15 hours for reaction;
[0052] After the reaction is completed, the lower precipitate is removed, anhydrous ethanol is added and stirred to obtain a mixed solution, and the mixed solution is centrifuged at 10000 rpm for 5 minutes to obtain a modified nano titanium oxide precipitate; the precipitate is dispersed in water to form a dispersion with a mass concentration of 5wt%, the pH is adjusted to about 10 with a 0.1M NaOH solution, and a transparent nano oxide dispersion is obtained by ultrasonic dispersion;
[0053] The nano-oxide dispersion is mixed with the aqueous polyurethane emulsion so that the mass of the nano-titanium oxide accounts for 5wt% of the mass of the polyurethane, and then the mixture is fully mixed by ultrasonication; the mixed solution is subjected to rotary evaporation at 60°C and 70rpm to remove excess water to obtain a nano-composite polyurethane coating;
[0054] The nano-composite polyurethane coating is applied to a glass substrate with a coating thickness of 200 μm. Its transmittance and reflectivity are measured after curing, and it is found that the transparency in the visible light range is significantly reduced, the transmittance fluctuates greatly between 35% and 90%, the transmittance is 65% at a wavelength of 500nm, and the reflectivity is 56.5% (635nm); the nano-composite polyurethane coating is applied to a resin substrate such as PC with a coating thickness of 200 μm, and affixed to an electronic display screen to significantly enhance the interaction effect between the electronic display screen and the laser pen light spot, but the low transparency affects the content presentation effect of the electronic display screen.
[0055] Comparative Example 1
[0056] Use polyurethane coating without nanoparticles.
[0057] The aqueous polyurethane emulsion was subjected to rotary evaporation at 60° C. and 70 rpm to remove excess water to make its viscosity the same as that of Examples 1 to 4, thereby obtaining a polyurethane coating;
[0058] The polyurethane coating is applied to a glass substrate with a coating thickness of 200μm. After curing, its transmittance and reflectivity are measured, and the transparency in the visible light range is very good, the transmittance in the visible light range reaches 100%, and the reflectivity is about 52%; the nano-composite polyurethane coating is applied to a resin substrate such as PC with a coating thickness of 200μm, and affixed to an electronic display screen has no effect on the interaction effect between the electronic display screen and the laser pen light spot.
[0059]
[0060]
[0061] Titanium dioxide prepared by the in-situ modification method of citric acid can greatly save time and improve modification efficiency compared to the common modification method of citric acid; and the in-situ modification method can obtain nano titanium dioxide with smaller particle size and narrower particle size distribution, thereby obtaining a more transparent and stable aqueous dispersion in the alkaline range. Titanium dioxide aqueous dispersion is blended with waterborne polyurethane to obtain a nano-composite polyurethane coating material. The refractive index of the nano-composite polyurethane coating is adjusted by the high refractive index and addition amount of titanium dioxide, thereby adjusting the diffuse reflection performance of the composite material; the nano-composite polyurethane coating is coated on a resin base film to obtain an optical film material, which improves the diffuse reflection performance of the film material while ensuring transparency, thereby enhancing the interactive effect between the electronic display screen and the laser pen light spot at all angles.
[0062] It can be seen from the above table that, compared with the comparative example, Examples 1 to 4 add a nano-oxide dispersion containing nano-titanium oxide obtained by a coating material preparation method for enhancing the interaction effect between an electronic display screen and a laser pen light spot of the present application to the aqueous polyurethane emulsion, and the reflectivity is enhanced, that is, the interaction effect between the electronic display screen and the laser pen light spot is enhanced. However, as the proportion of nano-titanium oxide in the mass of the aqueous polyurethane increases, the transmittance gradually decreases, that is, the optical film material made of a nano-composite polyurethane coating with a high nano-titanium oxide content is attached to the electronic display screen, which will affect the content presentation effect of the electronic display screen. Therefore, a nano-composite polyurethane coating in which nano-titanium oxide accounts for 1wt% of the mass of the aqueous polyurethane is selected, which can not only enhance the interaction effect between the electronic display screen and the laser pen light spot, but also ensure the content presentation effect of the electronic display screen.
[0063] The embodiments of the present application are described above. In the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present application is not limited to the above-mentioned specific implementation methods. The above-mentioned specific implementation methods are merely illustrative and not restrictive. Under the guidance of the present application, ordinary technicians in this field can also make many forms without departing from the purpose of the present application and the scope of protection of the claims, all of which are within the protection of the present application.
Claims
1. A method for preparing a coating material for enhancing the interaction effect between an electronic display screen and a laser pen light spot, characterized in that , including the following steps: S1: Tetrabutyl titanate, anhydrous ethanol, glacial acetic acid, citric acid and water are mixed in a certain proportion to form a mixed solution, and then the mixed solution is fully stirred and mixed; S2: placing the fully stirred and mixed solution into a hydrothermal kettle with a polytetrafluoroethylene liner, and placing the hydrothermal kettle in an oven for heating; S3: After the reaction is completed, the precipitate is washed by centrifugation, dispersed in water, adjusted to alkaline, and ultrasonically dispersed to obtain a transparent nano-oxide dispersion; S4: Mix the transparent nano oxide dispersion with the aqueous polyurethane emulsion, perform ultrasonication, and perform rotary evaporation to remove excess water to obtain a nano composite polyurethane coating material.
2. The method for preparing a coating material for enhancing the interaction effect between an electronic display screen and a laser pen light spot according to claim 1, characterized in that: In step S1, the mass ratio of tetrabutyl titanate, anhydrous ethanol, glacial acetic acid, citric acid and water is 0.98:23.68:1.04:0.2-1:1.
2.
3. The method for preparing a coating material for enhancing the interaction effect between an electronic display screen and a laser pen light spot according to claim 1, characterized in that: In step S3, the pH value is adjusted to an alkaline range of 8-11.
4. The method for preparing a coating material for enhancing the interaction effect between an electronic display screen and a laser pen light spot according to claim 1, characterized in that: In step S4, the rotary evaporation speed is 70 r / min and the temperature is 50° C.-70° C.
5. The method for preparing a coating material for enhancing the interaction effect between an electronic display screen and a laser pen light spot according to claim 1, characterized in that: In step S4, the mixing ratio of the nano-oxide dispersion and the aqueous polyurethane emulsion is such that the mass percentage of the nano-titanium oxide to the mass percentage of the aqueous polyurethane is greater than 0wt% and less than or equal to 5wt%.
6. The method for preparing a coating material for enhancing the interaction effect between an electronic display screen and a laser pen light spot according to claim 5, characterized in that: In step S4, the mixing ratio of the nano-oxide dispersion and the aqueous polyurethane emulsion is 1 wt % of the mass of the nano-titanium oxide to the mass of the aqueous polyurethane.
7. A coating material, characterized in that: The coating material is prepared by the method for preparing the coating material according to any one of claims 1 to 6.
8. An optical film material, characterized in that: The coating material as claimed in claim 7 is applied to the surface of a substrate and cured.
9. The optical film material according to claim 8, characterized in that: The substrate is PC, PET or PVC.
10. The optical film material according to claim 7, characterized in that: The coating thickness of the nano composite polyurethane coating material on the surface of the substrate is 25 μm-300 μm.